Karakter Kuantitatif Kacang Hijau pada Lingkungan Naungan - Sundari, Titik (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Tolerance to shade among mungbean genotypes were assessed based on their environmental stress tolerance indices (ITC). Through an approach of direct and indirect relationships between quantitative characters, quantitative characters that play roles in mungbean tolerance to shade was identified. The trial was conducted at Kendalpayak Experimental Farm, Malang. Treatments were without shading and with a 52% shading using 12 mungbean genotypes representing 9 genotypes tolerant to shading and susceptible genotypes. Under each shaded environment, the treatments were arranged in a randomized block design with three replications. Observations were carried out on plant morphology (leaf number, leaf area, specific leaf area, leaf hairs number, plant height, stem diameter, age of flowering and harvesting, number of pods, pod dry weight, seed weight and seed size) and leaf anatomy (thickness of leaves, epiderm cells, palisade tissue length, and number of leaf stomates). Mungbean genotypes that were tolerant to shading had different plant morphology and leaf anatomy from those of susceptible genotypes. The tolerant mungbean genotypes had larger leaves, less number of leaf hairs, thicker leaves, thinner leaf epidermal cells, longer palisade tissue, more number of stomates, higher contents of chlorophyll a and b, larger diameter of stem, higher pod dry weight, larger seed size, and higher grain yields than those of the susceptible genotypes. Three characters of mungbean plants that need to be taken into account in determining tolerance to shade were the leaf area, number of leaf hairs, and seed weight per plant. Selection of the immatured beans can be done using indirect selection based on the three characters, namely stem diameters at 2 and 4 weeks after planting (WAP), plant height at 4 WAP, and weight of 100 seeds.